RealDB: a genome and transcriptome resource for the red algae (phylum Rhodophyta). (17th July 2018) - Chen, Fei; Zhang, Jiawei; Chen, Junhao; Li, Xiaojiang; Dong, Wei; Hu, Jian; Lin, Meigui; Liu, Yanhui; Li, Guowei; Wang, Zhengjia; Zhang, Liangsheng
Abstract: With over 6000 species in seven classes, red algae (Rhodophyta) have diverse economic, ecological, experimental and evolutionary values. However, red algae are usually absent or rare in comparative analyses because genomic information of this phylum is often under-represented in various comprehensive genome databases. To improve the accessibility to the ome data and omics tools for red algae, we provided 10 genomes and 27 transcriptomes representing all seven classes of Rhodophyta. Three genomes and 18 transcriptomes were de novo assembled and annotated in this project. User-friendly BLAST suit, Jbrowse tools and search system were developed for online analyses. Detailed introductions to red algae taxonomy and the sequencing status are also provided. In conclusion, realDB (realDB.algaegenome.org) provides a platform covering the most genome and transcriptome data for red algae and a suite of tools for online analyses, and will attract both red algal biologists and those working on plant ecology, evolution and development. Database URL: http://realdb.algaegenome.org/